2021
DOI: 10.3168/jds.2020-18981
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter and airborne endotoxin concentration in calf barns and their association with lung consolidation, inflammation, and infection

Abstract: Agricultural operations are important sources of organic dust containing particulate matter (PM) and endotoxins, which have possible negative health consequences for both humans and animals. Dust concentrations and composition in calf barns, as well as the potential health effects for these animals, are scarcely documented. The objective of this study was to measure PM fractions and endotoxin concentrations in calf barns and study their associations with lung consolidation, respiratory tract inflammation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…transport, commingling, feed and water deprival, dehorning). Beside clinical outbreaks, a substantial number of calves also suffers from subclinical pneumonia (van Leenen et al, 2020(van Leenen et al, , 2021. In addition, sporadic cases in adult animals have also been described (Dorso et al, 2021).…”
Section: Results Of the Elr By Bacteriummentioning
confidence: 99%
“…transport, commingling, feed and water deprival, dehorning). Beside clinical outbreaks, a substantial number of calves also suffers from subclinical pneumonia (van Leenen et al, 2020(van Leenen et al, , 2021. In addition, sporadic cases in adult animals have also been described (Dorso et al, 2021).…”
Section: Results Of the Elr By Bacteriummentioning
confidence: 99%
“…Several studies have reported that PM10 contains endotoxins that act as LPS stimuli to induce inflammation [ 42 , 43 ]. In addition, the activation of macrophages by endotoxins (i.e., LPS) is a major inflammatory induction mechanism [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activation of macrophages by endotoxins (i.e., LPS) is a major inflammatory induction mechanism [ 44 ]. Notably, NO plays a key role in inflammatory responses, and cytokine-activated macrophages trigger NO release [ 43 ]. In this study, the CJB extract treatment decreased NO production in the RAW264.7 mouse macrophages in LPS induction ( Figure 6 b).…”
Section: Discussionmentioning
confidence: 99%
“…Given that RIs transmit primarily via the airborne route, the risk factors associated with RIs are those influencing airborne transmission such as air pathogen concentrations (Lago et al, 2006), air endotoxin and particulate matter concentrations (van Leenen et al, 2021), sharing air space with older cattle (Medrano‐Galarza et al, 2018), pen stocking rate (Svensson & Liberg, 2006) and calf housing design (Gorden & Plummer, 2010). Additionally, as with most neonatal infectious diseases, FPT is a risk factor for RI (Deepak et al, 2021) as is co‐infection with multiple respiratory pathogens (Deepak et al, 2021) and co‐morbidity with GI infections (Lorenz et al, 2021).…”
Section: Neonatal Bovine Morbiditiesmentioning
confidence: 99%